Leah Price, What we talk about when talk about books, Nowy Jork: Basic Books 2019, s. 215. ISBN 978-0-465-04268-5 - Szary-Matuszkowiak, Diana (Biblioteka, 2021)
Recenzja: Leah Price, What we talk about when talk about books, Nowy Jork: Basic Books 2019, s. 215. ISBN 978-0-465-04268-5